2016
DOI: 10.1097/meg.0000000000000551
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patients at higher risk of hepatocellular carcinoma recurrence after liver transplantation in a multicenter cohort study from Argentina

Abstract: This scoring model may be a useful additional tool for HCC recurrence risk stratification before LT. Prospective studies are needed to evaluate our model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…The second major finding in this study is that pre‐transplant AFP level is associated with earlier time to HCC recurrence, possibly related to the previously described association between increased AFP and features of tumor aggressiveness . Although numerous prior studies have found pre‐transplant AFP to be a positive risk factor for HCC recurrence, no studies have explicitly evaluated the time at which those recurrences occur as a function of AFP. Interestingly, restricting the cohort to recurrences within 60 or 36 months attenuated the association, indicating that elevated pre‐transplant AFP confers increased risk of HCC recurrence even at longer timepoints.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The second major finding in this study is that pre‐transplant AFP level is associated with earlier time to HCC recurrence, possibly related to the previously described association between increased AFP and features of tumor aggressiveness . Although numerous prior studies have found pre‐transplant AFP to be a positive risk factor for HCC recurrence, no studies have explicitly evaluated the time at which those recurrences occur as a function of AFP. Interestingly, restricting the cohort to recurrences within 60 or 36 months attenuated the association, indicating that elevated pre‐transplant AFP confers increased risk of HCC recurrence even at longer timepoints.…”
Section: Discussionmentioning
confidence: 50%
“…For additional analyses, we also categorized etiology of liver disease as viral or non‐viral. Maximum pre‐transplant AFP was binned into a four‐level categorical variable, with levels adapted from prior studies (≤20ng/mL, 21‐99ng/mL, 100‐499ng/mL, and ≥500ng/mL) . We also obtained AFP levels immediately prior to LT for a sensitivity analysis (detailed below), although studies suggest that maximum and immediate pre‐LT AFP perform similarly in HCC recurrence models .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Etiologies of liver disease were classified as hepatitis C virus (HCV), hepatitis B virus (HBV), ethanol (EtOH), nonalcoholic fatty liver disease (NAFLD), autoimmune (including autoimmune hepatitis, primary biliary cirrhosis, and primary sclerosing cholangitis), and others (composed of numerous less common etiologies, including hemochromatosis, sarcoidosis, alpha‐1‐antitrypsin, and rare inborn metabolic liver diseases). Maximum pretransplant AFP (maximum AFP) was classified as a 4‐level categorical variable (<100, 101‐499, 500‐1000, and >1000 ng/mL), adapted from numerous prior studies . The maximum AFP variable performs similarly to AFP immediately prior to transplant (pretransplant AFP) in HCC recurrence models, and it reflects current OPTN policy which provisionally disallows standard exception points for patients with maximum AFP >1000 ng/mL .…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have aimed to identify predictors of HCC recurrence to improve LT patient selection and minimize adverse outcomes. Risk prediction has focused on pretransplant laboratory criteria (eg, alpha‐fetoprotein [AFP]), imaging criteria, and explant pathology . These findings have LT selection implications because they inform Organ Procurement and Transplantation Network (OPTN) HCC exception policies, such as those for patients with high AFP levels (>1000 ng/mL) .…”
mentioning
confidence: 99%